STRATEGI KOMUNIKASI BPP (BALAI PENYULUHAN PERTANIAN) KECAMATAN KABAWETAN DALAM MEBANGUN CITRA PADA KELOMPOK TANI DESA TANGSI DUREN (Studi Kasus Kelompok Tani Desa Tangsi Duren) - Mulyana, Yogi; Putra, Afdal Makkuraga (Universitas Mercu Buana, 2023)
Based on the issue that spread among the Tangsi Duren Village Community that the Farmer Group Institution only moves when assistance is available, in this issue the BPP (Agricultural Extension Center) of Kabawetan District is responsible for this because the BPP is an institution that goes directly to farmers or farmer groups giving directions and information. The research method used is a case study with a qualitative descriptive approach. The research paradigm is constructivist. The results showed that the application of the BPP Communication Strategy in Kabawetan District in building the image of the Tangsi Duren Village farmer group was able to improve the image of the farmer group so that it was active in group activities. This is proven by the results of interviews with the Communication Strategy Coordinator of the BPP Kabawetan who have carried out 5 stages in the communication strategy, namely: (1). In research, BPP always conducts group viewing activities every month (2). Planning, where extension workers always see situations where they can achieve messages so that they can be received (3). Implementation, agricultural extension workers always urge in every event or activity the importance of being active in groups (4). Evaluation extension agents always evaluate the group every month (5) Reporting, the form of reporting on this activity is in the farmer group activity book. Then the researcher suggests that in implementing activities using visual media so that the communication strategy is more effective.